PENERAPAN INOVASI SUPERVISI AKADEMIK UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI MAN 2 KOTA MALANG - Rina Widjajanti (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
The results showed that; 1) Planning for academic supervision by the principal at MAN 2 Malang City uses a collaborative approach model, which is compiled at the beginning of the year. The types of programs include annual programs, programs are prepared based on identification, analysis and evaluation of the previous year. The results show that planning for academic supervision in the post-Covid-19 transition period is currently going well. 2) Implementation of academic supervision in order to improve the quality of learning in MAN 2 Malang City using the academic supervision model. The results of the research on the implementation of academic supervision in the post-Covid-19 transition era by the head of the madrasah continued well. This can be seen from the direct supervision process in the form of monitoring the teacher's teaching activities through direct observation, the supervisor will provide assistance to the teacher in solving problems and providing an evaluation of the learning process that has taken place. 3) Evaluation of the academic supervision of the madrasah principal is carried out by the madrasa head and the supervision team at MAN 2 Malang City, carried out at the end of the semester to measure the success of a supervisory approach that has been carried out by the madrasah principal.Keywords: Academic Supervision Innovation, learning quality.